PELATIHAN DIGITALISASI PENGARSIPAN DATA PENDUDUK DAN PELAYANAN PENGAJUAN SURAT DI DESA BLULUK - Arezqi Tunggal Asmana; Ahmad Sholikin; Ahmad Dani Fahrudin; Vella Sufa Habibah; Arneta Mei Vella (LPPM Universitas Islam Darul 'Ulum Lamongan, 2023)
Archiving data on residents of Bluluk Village and writing letters manually are considered to be less effective and less efficient. In addition to the bureaucracy that takes up a lot of space, writing letters manually takes a lot of time. Innovation using simple technology really needs to be utilized, in order to help the community and Bluluk village officials. Real Work Lecture (KKN) activities for Darul Ulum Lamongan Islamic University students held training on archiving digitization and the process of submitting letters as a work program by the Digital Village team in Bluluk Village. This study uses a qualitative method. The purpose of this digitization training activity is to streamline and streamline the process of data archiving and submission of letters. This can be marked by the administrative process for submitting letters that is shorter and can be done anywhere. The public only needs to take the letter if the letter submission has been validated by an authorized device. The results of filling in the recitation of letters from residents can be printed directly without making a detailed letter per submission.